Renal protection during 177lutetium DOTATATE molecular radiotherapy in children: a proposal for safe amino acid infusional volume during peptide receptor radionuclide therapy. Issue 2 (February 2022) - Taylor, Catherine A.; Shankar, Ananth; Gaze, Mark N.; Peet, Connie; Gains, Jennifer E.; Wan, Simon; Voo, Stefan; Priftakis, Dimitrios; Bomanji, Jamshed B.
Abstract : Peptide receptor radionuclide therapy (PRRT) using radiolabelled somatostatin analogues such as 177-lutetium DOTATATE is an effective treatment modality for neuroendocrine tumours, paragangliomas, and neuroblastomas. However, renal and haematopoietic toxicities are the major limitations of this therapeutic approach. The renal toxicity of PRRT is mediated by renal proximal tubular reabsorption and interstitial retention of the radiolabelled peptides resulting in excessive renal irradiation that can be dose-limiting. To protect the kidneys from PRRT-induced radiation nephropathy, basic amino acids are infused during PRRT as they competitively bind to the proximal tubular cells and prevent uptake of the radionuclide. In adults, 1 L of a basic amino acid solution consisting of arginine and lysine is infused over 4 h commencing 30 min prior to PRRT. However, this volume of amino acids infused over 4 h is excessive in small children and can result in hemodynamic overload. This is all the more relevant in paediatric oncology, as many of the children may have been heavily pretreated and so may have treatment-related renal and or cardiac impairment. We have therefore developed the following guidelines for safe paediatric dosing of renal protective amino acid infusions during PRRT. Our recommendations have been made taking into consideration the renal physiology in small children and the principles of safe fluid management in children.